2014
DOI: 10.1111/cen.12555
|View full text |Cite
|
Sign up to set email alerts
|

Three novel IGF1R mutations in microcephalic patients with prenatal and postnatal growth impairment

Abstract: These variations led to failure of the IGF1R function causing pre- and postnatal growth retardation and microcephaly. Microcephaly should be considered in the evaluation of SGA patients, because it seems to favour the frequency of detection of IGF1R mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…[32] Microcephaly, pre-and postnatal growth retardation were found in patients with heterozygous missense mutations in three unrelated patients, de novo p.Arg1256Ser, de novo p.Asn359Tyr and p.Tyr865Cys. [33] We checked the exon 2 of the IGF1R gene for possible genetic alterations and found no alterations.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Microcephaly, pre-and postnatal growth retardation were found in patients with heterozygous missense mutations in three unrelated patients, de novo p.Arg1256Ser, de novo p.Asn359Tyr and p.Tyr865Cys. [33] We checked the exon 2 of the IGF1R gene for possible genetic alterations and found no alterations.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in (Aleman and Torres-Aleman 2009), there are numerous studies supporting a critical role for IGF-1 in normal brain development and function. Clinical studies have shown that point mutations in both the IGF-1 and IGF-1R genes result in decreased IGF-1 signaling and lead to microcephaly and mental impairment (Abuzzahab et al 2003; Bonapace et al 2003; Gannage-Yared et al 2013; Juanes et al 2014; Netchine et al 2009; Walenkamp et al 2005; Woods et al 1996). These patients often exhibit significant delays in psychomotor function and hearing loss (Bonapace et al 2003; Walenkamp et al 2005).…”
Section: Gh/igf-1 Regulation Of Neuronal Development Structure and mentioning
confidence: 99%
“…STAT5 proteins contribute to the common pathway of growth hormone and interleukin-2 cytokine family signaling, therefore mutations in STAT5B cause growth failure and immune deficiency [142]. Mutations in IGF1 or IGF1R cause intrauterine growth restriction (because IGF1 signaling is important for intrauterine growth while GH is not required), postnatal growth failure, microcephaly and other various anomalies including developmental delay [143147]. Mutations in a gene that stabilizes IGF-1, IGFALS, forming an IGF-1-IGFBP3-ALS complex, cause growth deficiency, insulin resistance and osteoporosis [148149].…”
Section: Genetics Of Short Staturementioning
confidence: 99%